BASIC MARKETING: A GLOBAL - MANAGERIAL APPROACH - Perreault, William D., Jr., author 361786; McCarthy, E. Jerome (Edmund Jerome), author 278654 (Boston, Mass. : McGraw-Hill, 2005)
Includes bibliographical references (p. 725-787) and indexes